2012
DOI: 10.5194/isprsarchives-xxxix-b1-115-2012
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Landnet Sites Focusing on Tuz Gölü Salt Lake, Turkey

Abstract: Abstract. Radiometric calibration is critical to ensure the accuracy, veracity, continuity and reliability of satellite data measured from multiple sensors and platforms, and is thus recognized as a key activity by all satellite operators. For imaging sensors, vicarious methods using natural targets (such as salt lakes, deserts, or flatlands that are well-characterized and preferably temporally and spatially stable) as a reference are similarly well established. However, while selecting a target site, it is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, according to Gürbüz et al [6] and CEOS [31], the calibration site presents some debris from weapon tests; this can be another possible factor influencing the response of some validation samples at the sub-pixel level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, according to Gürbüz et al [6] and CEOS [31], the calibration site presents some debris from weapon tests; this can be another possible factor influencing the response of some validation samples at the sub-pixel level.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially valid when the information provided by a specific mission must be integrated with data from other platforms, either into models or multitemporal datasets [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, CV s is related to the pixel size or window size. Gürbüz et al investigated this effect using multi-scale HRV (High Resolution Visible), TM (Thematic Mapper), and AVHRR image data acquired over the Railroad Valley Playa (NV, USA) test site [39], one of eight well-characterized calibration test sites (known as a LANDNET site) endorsed by the Infrared Visible Optical Sensors (IVOS) subgroup of the CEOS [1,35]. The results indicated that the CV s were <1.5% when HRV and TM data with smaller pixel sizes (30 m) were used but increased to 2.5-3.5% when AVHRR data with a larger pixel size (1.1 km) were used.…”
Section: (4 D × 4 Y)mentioning
confidence: 99%